Who Can Publish Decolonized Ethnography and Cultural Theory with the Anger it Deserves? Unclassified Lloronas and the Academic Text - Lavie, Smadar (Vilnius University Open Series, 2025)
Gloria Anzaldúa’s autohistoria-teoria presents subaltern theorization and autoethnography as testimony. Nevertheless, subaltern women anthropologists from the Global South are not part of the North American ‘woman of color’ classification of Latinas, African-Americans, and Asians. They are therefore expected to use the U.S.-U.K. formula of dispassionate (post)colonial scholarship. The underlying assumption for the unclassified woman ethnographer from the Global South is that she comes from her country’s cosmopolitan elite. She is therefore required to deploy the detached Northern social science language. This paper calls academic publishers to remove the elite label from the unclassified Women-of-Color authorship, and publish them in the decolonized, emotive Anzaldúa auto-ethnography of bearing witness.